2002
DOI: 10.1016/s1074-7613(02)00273-x
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance to Islet Antigens and Prevention from Diabetes Induced by Limited Apoptosis of Pancreatic β Cells

Abstract: Crosspresentation of self-antigens by antigen-presenting cells is critical for the induction of peripheral tolerance. As apoptosis facilitates the entry of antigens into the crosspresentation pathway, we sought to prevent the development of autoimmune diabetes by inducing pancreatic beta cell apoptosis before disease onset. Accordingly, young nonobese diabetic (NOD) mice injected with a single low dose of streptozotocin (SZ), a drug cytotoxic for beta cells, exhibited impaired T cell responses to islet antigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
129
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(138 citation statements)
references
References 48 publications
8
129
0
Order By: Relevance
“…Nevertheless, previous studies have demonstrated that DCs are the predominant cell type that presents islet-derived self-antigens (24)(25)(26)(27). To determine whether the cells responsible for presentation here were DCs, CD11c-DTR3RIP-OVA lo bone marrow chimeras were generated.…”
Section: Ctl Damage Induces Antigen Releasementioning
confidence: 99%
“…Nevertheless, previous studies have demonstrated that DCs are the predominant cell type that presents islet-derived self-antigens (24)(25)(26)(27). To determine whether the cells responsible for presentation here were DCs, CD11c-DTR3RIP-OVA lo bone marrow chimeras were generated.…”
Section: Ctl Damage Induces Antigen Releasementioning
confidence: 99%
“…Activation of caspases may be achieved by several molecular pathways; the best known stimuli triggering the caspase cascade are stimulation of Fas or TNF receptors, release of cytochrome c from the cellular mitochondria, and exposure to granzymes, which are secreted by cytotoxic T cells (3,12,31,37,54). Detailed research on the mechanisms controlling caspase activity will provide better insight into the pathogenesis of autoimmune diseases with special reference to estrogen deficiency.…”
mentioning
confidence: 99%
“…This limited and arrested in vivo proliferation followed by T-cell deletion has been associated with induction of tolerance. [18][19][20] Activated splenic CD4 + KJ1-26 + cells after intrasplenic immunization with T/SA-OVA secrete IL-10 and IL-4 and not IFN-g…”
Section: Splenic Cd11c and Cd4 T-cell Interaction And Tumour Cell Vacmentioning
confidence: 99%
“…It is controversial whether CD8 + T-cell tolerance [18][19][20] results from an interaction between CD8 + T cells and immature CD11c + cells 21 or quite the reverse, with mature CD11c + cells. 22 However, in both cases, one can assume that CD4 + T-cell tolerance ensues from an encounter with immature CD11c + cells and this may generate regulatory T cells.…”
Section: Introductionmentioning
confidence: 99%